Effect of food texture on impression formation and prosocial behaviors - Tan, Kah Min (2016)
It is widely documented that metaphors influence our thoughts and social behaviors through bodily experiences (embodied cognition). Recent research has shown that the haptic experience of texture can be embodied in interpersonal judgments and decisions. Many studies have showcased that particular tastes can influence judgements and behaviors but no studies to date has explored the extent to which how food texture can affect social perception and in turn influence behaviors. The present study seeks to investigate the metaphorical link between food texture and social perception along with social behaviors. The study examined prosociality and personality judgments as specific social outcomes of eating hard/soft food. We are interested in exploring whether consuming hard/soft food would result in a metaphoric transfer within individuals and consequently influence their impression formation of others and prosocial behaviors toward others. Participants ate either hard or soft test foods provided while interacting with another participant for 10 minutes, completed a series of questionnaires and played an Investment Game. Results showed that participants in the soft food manipulation were more prosocial toward others by donating more time to volunteer at a charity event. Contrary to what was expected, the results revealed that participants in the soft food manipulation did not form a more positive impression of their interaction partner and were not more prococial toward their interaction partner (in terms of trust, reciprocity and cooperation). Implications of the current finding in on-the-ground social marketing strategy and one’s food choices during social interactions are discussed.